2010
DOI: 10.4067/s0717-95022010000100016
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Sugar Residues in the Stomach of Three Species of Monkeys (Tupaiidae glis, Nycticebus cocang and Callithrix jacchus) by Lectin Histochemistry

Abstract: The stomach of three species of non-human primates was investigated by lectin histochemistry to clarify the staining affinity and distribution patterns of their sugar residues. All gastric regions, with little differences between the deep and superficial parts of the same region, were rich in. in N-acetylglucosamine and/or neuraminic acid. Although, the superficial regions of the gastric mucosa were scanty in N-acetylgalactosamine, a-D-glucose and a -D-mannose, the deep parts of the gastric mucosa were rich in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
1
5
1
Order By: Relevance
“…The study on gnotobiotic pig revealed normal structure of lymph nodes in submucosa of cardiac region of stomach and could migrate to mucosa layer [ 29 ]. The similar result can be found in monkey [ 30 ]. Therefore it is probable that the stomach structure was not only designed for digestion but also genetically immunology contributed.…”
Section: Discussionsupporting
confidence: 87%
“…The study on gnotobiotic pig revealed normal structure of lymph nodes in submucosa of cardiac region of stomach and could migrate to mucosa layer [ 29 ]. The similar result can be found in monkey [ 30 ]. Therefore it is probable that the stomach structure was not only designed for digestion but also genetically immunology contributed.…”
Section: Discussionsupporting
confidence: 87%
“…In L. maximus , the pyloric glands, branched tubular and tortuous, showed a narrower lumen than the cardiac glands, straight simple and unbranched. These results differ from those observed in the pyloric glands of the stomachs of monkeys ( Tupaiidae glis , Nycticebus cocang and Callithrix jacchus ; Fayed et al., 2010) and of brown rats ( Rattus norvegicus ; Chandana et al., 2013), which are simple tubular and short.…”
Section: Discussioncontrasting
confidence: 60%
“…The great quantity of mucous cells both in the cardiac and pyloric regions of mammals indicates the secretion of high levels of mucins to neutralize the corrosive and harmful effect of hydrogen chloride and pepsin from the gastric juice, thus helping to maintain the normal levels of pH in this organ (Fayed et al., 2010; Igbokwe & Obinna, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations